Causes of death and predictors of survival after aortic valve replacement in low flow vs. normal flow severe aortic stenosis with preserved ejection fraction - Eleid, Mackram F. (Eur Heart J Cardiovasc Imaging, 2015)
AIMS: Reduced stroke volume index (SVI) in patients with severe aortic stenosis (AS) and preserved ejection fraction (EF) is associated with adverse outcomes even after aortic valve replacement (AVR), although specific reasons for impaired survival in this group are unknown. We investigated predictors of post-AVR survival and specific cause of death in patients with AS according to SVI. METHODS AND RESULTS: Among 1120 consecutive patients with severe AS (aortic valve area <1.0 cm(2)) and preserved EF (≥50%) using 2-D and Doppler echocardiography who had AVR, 61 (5%) patients had reduced SVI [<35 mL/m(2) (low flow, LF)] and 1059 (95%) had normal SVI [≥35 mL/m(2) (normal flow, NF)]. Survival post-AVR was lower in patients with LF compared with NF [3-year survival in LF group 76% (95% CI 70–82) vs. 89% (95% CI 88–90%), P = 0.03] primarily due to higher cardiac mortality [3-year event rate 13% (95% CI 8–18%) in LF vs. 5% (95% CI 5–7%) in NF, P = 0.02]. Congestive heart failure (CHF) was the most common cause of cardiac death in the LF group (57% of post-AVR cardiac deaths) and was a more frequent cause of death in LF compared with NF (3-year risk 7 vs. 2%, P = 0.008). Multivariable predictors of post-AVR mortality included age, creatinine, haemoglobin, right ventricular systolic pressure, SVI, and cognitive impairment. CONCLUSION: Reduced SVI is associated with higher cardiac mortality after AVR. CHF is the predominant cause of cardiac mortality after AVR in patients with LF, suggesting the presence of persistent myocardial impairment in this population.